0105 Farm exposures, allergy symptoms and risk of non-Hodgkin lymphoma in the Agricultural Health Study. (23rd June 2014) - Hofmann, Jonathan; Hoppin, Jane; Blair, Aaron; Alavanja, Michael; Beane Freeman, Laura
Abstract : Objectives: Exposure to allergens and microorganisms in the agricultural environment has been linked to altered immune response. Studies in the general population have reported reduced risks of non-Hodgkin lymphoma (NHL) among those with a history of atopic conditions, although results are inconsistent. To evaluate the allergy-NHL association in the context of farm exposures, we conducted an investigation in the Agricultural Health Study, a prospective cohort of farmers and spouses from North Carolina and Iowa. Method: Our study included 49 656 farmers and spouses with crop and animal exposures and allergy symptoms reported at baseline (1993–1997). We identified 418 incident cases of NHL (including chronic lymphocytic leukaemia and multiple myeloma) during follow-up through 2010 in North Carolina and 2011 in Iowa. Hazard ratios (HR) and 95% confidence intervals (CI) were calculated using multivariable-adjusted proportional hazards models. Results: At enrollment, over 80% of the study participants lived on farms growing grains or hay and 64% on farms raising livestock. Compared to individuals without allergy symptoms, those with symptoms had a reduced risk of NHL (HR=0.61, 95% CI=0.50–0.74). We observed a slightly greater reduction in NHL risk among participants whose allergy symptoms worsened after working with grains and hay (HR=0.53, 95% CI=0.41–0.69). The association between livestock and NHL was borderline significant overall (HR=0.82, 95% CI=0.66–1.01), and significant among those without allergy symptoms (HR=0.70, 95% CI=0.51–0.96). Conclusions: Our findings suggest that among individuals working and living on farms, allergy symptoms are associated with a reduced risk of developing NHL, and that risk may be influenced by particular farm characteristics.